A phase 2b, randomized, double‐blind, multicenter, vehicle‐controlled study to assess the efficacy and safety of two crisaborole regimens in Japanese patients aged 2 years and older with mild‐to‐moderate atopic dermatitis. Issue 11 (26th August 2021) - Fujita, Kayo; Yagi, Michio; Moriwaki, Shinichi; Yoshida, Mizuki; Graham, Daniela
Abstract: Atopic dermatitis (AD) is a chronic inflammatory skin disease characterized by pruritus, xerosis, and eczematous lesions. In Japan, treatment options, such as topical corticosteroids and tacrolimus, are associated with efficacy and safety concerns. Crisaborole ointment, 2%, is a topical non‐steroidal anti‐inflammatory agent approved in several countries for the treatment of mild‐to‐moderate AD. This phase 2b, randomized, double‐blind study (NCT03954158) assessed the efficacy and safety of two crisaborole regimens versus vehicle in the treatment of Japanese patients aged ≥2 years with mild‐to‐moderate AD. Each patient was assigned to one of two age cohorts (≥12 or 2–11 years) and randomized to crisaborole once daily (QD) or twice daily (BID). All patients had two target lesions that were each randomly assigned to crisaborole or vehicle at baseline and treated for 2 weeks. The primary endpoint was change from baseline in total sign score (TSS) in crisaborole‐ or vehicle‐treated target lesions on day 15, and secondary endpoints included change from baseline in Investigator's Static Global Assessment (ISGA) and pruritic assessments (Cohort 1: peak pruritus numeric rating scale [NRS]; Cohort 2: Itch Severity Scale Self‐Report and Caregiver‐Reported Itch Severity NRS) and incidence of treatment‐emergent adverse events (TEAEs). This study comprised 81 patients (Cohort 1: n = 41; Cohort 2: n = 40). Crisaborole‐treated lesions showed statistically significant reductions in TSS versus vehicle‐treated lesions at day 15 ( p < 0.01), and numerically larger decreases in TSS were observed with crisaborole BID versus crisaborole QD in both cohorts. Furthermore, crisaborole‐treated lesions generally demonstrated greater decreases in ISGA, peak pruritus NRS, Itch Severity Scale, and Caregiver‐Reported Itch Severity NRS versus vehicle‐treated lesions irrespective of regimen or cohort. Overall, TEAEs were mild; the most frequently reported TEAEs was application site irritation. In summary, both crisaborole regimens, particularly crisaborole BID, demonstrated efficacy and were well tolerated.